2012 IEEE International Conference on Power Electronics, Drives and Energy Systems (PEDES) 2012
DOI: 10.1109/pedes.2012.6484421
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of axial flux SRM topologies for electric vehicle application

Abstract: In-wheel motors for electric vehicles (EVs) have a high outer diameter (D) to axial length (L) ratio. In such applications, axial flux machines are preferred over radial flux machines due to high power density. Moreover, permanent magnet (PM)-less machines are gaining interest due to increase in cost of rare-earth PM materials. In view of this, axial flux switched reluctance motor (AFSRM) is considered as a possible option for EV propulsion. Two topologies namely, toothed and segmented rotor AFSRM are designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…As mentioned, the external radius and the axial length are the same in order to have the same volume (equations (2) and 3).…”
Section: Asrm Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, the external radius and the axial length are the same in order to have the same volume (equations (2) and 3).…”
Section: Asrm Modellingmentioning
confidence: 99%
“…In order to choose the appropriate structure for electric traction, comparisons between axial and radial SRM are essentially presented. Except some works like [2]- [4], the majority of studies on switched reluctance motor for an electric traction has been made by considering a radial structure [5]- [13]. Therefore, this work focuses on the axial structure for an automobile application.…”
Section: Introductionmentioning
confidence: 99%
“…Although reduced torque ripple is not important for the flywheel rotor itself (since these generally have a high moment of inertia), secondary benefits include decreased losses, decreased vibration and more constant charging and discharging rates. The characteristic ripple torque of axial flux SRMs has been a subject under study [44][45][46].…”
Section: Switched Reluctance Machinementioning
confidence: 99%
“…From literature, it can be observed that many works are related to radial flux SRM; however few works are related to axial flux SRM [3]. Some of them refer to axial flux SRM with two stators [4]- [6], but in this paper the motor has only one stator. With respect to the control strategies, several strategies are reported [7]- [9].…”
Section: Introductionmentioning
confidence: 96%